Biomaterials Electrodes for Degradation of Phenol (American International Journal of Biology and Life Sciences, 2019)
A novel bio electrode containing bacteria immobilized on clay mixed carbon paste electrode (Bactria-clay-CPE) is developed for detection and degradation of the phenolic solutions based on electrochemical techniques such cyclic voltammetry, square wave voltammetry, electroctrochemical impedence spectroscopy. The results obtained showed that bacteria-clay- CPE exhibited excellent electro-catalytic activity towards phenol. The recorded cyclic voltammogram shows that the oxidation of phenol is manifested by the appearance of four oxidation peaks.